Dipstick albuminuria and acute kidney injury recovery in critically ill septic patients. Issue 6 (June 2016) - Neyra, Javier A; Li, Xilong; Yessayan, Lenar; Adams‐Huet, Beverley; Yee, Jerry; Toto, Robert D
Abstract: Aim: Acute kidney injury (AKI) is a frequent complication of sepsis, a pro‐inflammatory state that alters tubular handling of filtered albumin. We hypothesized that dipstick albuminuria (DA) is associated with a lower rate of AKI recovery in septic patients. Methods: This was a single‐centre, retrospective cohort study of adults with sepsis‐associated AKI in an urban academic intensive care unit (ICU). Patients with unknown baseline serum creatinine (SCr), absent urinalysis, and those with estimated glomerular filtration rate (eGFR) <15 mL/min per 1.73m 2 or receiving chronic renal replacement therapy (RRT) were excluded. The independent variable was DA (negative or trace, 30 mg/dL, and ≥100 mg/dL) within the first 72 h of ICU stay. The outcome variable was AKI recovery at 30 days following hospital discharge, defined as the last SCr returning to a level less than 1.5 times the baseline SCr level and independence of RRT. Results: A total of 988 patients were included in the study. The median length of hospitalization was 11 days. The patients with higher degree of DA had worse critical illness scores. After adjustment for several confounders, DA ≥30 mg/dL was independently associated with "no AKI recovery" at 30 days post‐discharge (adjusted OR 1.40, 95% CI, 1.01–1.95 for DA =30 mg/dL and 1.67, 1.15–2.42 for DA ≥100 mg/dL, P = 0.02). Other independent predictors of "no AKI recovery" were cumulative fluid balance, Sequential Organ Failure Assessment (SOFA) score, exposure to diuretics, and the need for mechanical ventilation. Conclusion: Dipstick albuminuria ≥30 mg/dL is independently associated with lower rate of AKI recovery at 30 days post‐discharge. Our findings emphasize the potential utility of a simple routine test of DA in the risk‐stratification of AKI recovery in ICU septic patients. Summary at a Glance: In a study of 988 patients admitted with with septic AKI in ICU, the authors show that dipstick positive albuminuria is associated with a low rate of recovery at 30 days.